AUDIT OF SURGICAL EMERGENCY AT LAHORE GENERAL HOSPITAL - Khalid, Sadaf; Bhatti, Afsar Ali; ulhuq, Burhan (Journal of Ayub Medical College Abbottabad, 2015)
Background: Audit is a quality improvement process that seeks to improve patient care and outcomes through systematic review of care against explicit criteria and the review of change. Objective of this study was to report the patterns of admissions in our surgical emergency and the comparison of results with the available data Methods: All the patients presented in the surgical emergency of Unit III from April to December 2014. Detail of all surgical patients admitted during the period was recorded from the emergency entry register maintained by the staff nurse. Demographic data, mode of admission, diagnosis and outcomes were recorded on a pro forma. Results: Total number of patients were 11140, out of which 5998 (53.8%) were males and 5142 (46%) were females, mostly were between 18-56 years of age. Emergency surgeries were performed in 650 of our cases whereas the rest of the patients were managed conservatively, treated at minor operation theatre (MOT), referred to their concerned emergencies or discharged. The most common presentation was road traffic accidents followed by trauma, urological emergencies and intestinal obstruction. Overall mortality was estimated as 1.5%. Conclusions: Surgical audit should be made a regular practice to serve as an important and effective tool of accountibilty on clinical outcomes and self evaluation and in improving the quality of our health care system. Keywords: Surgical Audit, surgical emergency, outcomes